Safety outcomes associated with the moderna COVID-19 vaccine (mRNA-1273): a literature review - Angel Shabu; Prasad S. Nishtala (Taylor & Francis Group, 2023)
Introduction Current safety data from Phase 3 clinical trials have concluded that apart from transient local and systemic reactions, no safety concerns were identified for the Moderna COVID-19 vaccine (mRNA-1273). However, Phase 3 studies are insufficient to detect rare adverse events (AEs). A literature search of the two major electronic databases, Embase and PubMed, was performed to enable the identification and characterization of all relevant articles from December 2020 to November 2022. Areas Covered This narrative review summarizes the key safety outcomes associated with the mRNA-1273 vaccine to inform healthcare decisions and increase public awareness of mRNA-1273 vaccine safety. The primary adverse events (AEs) reported within a diverse population, receiving the mRNA-1273 vaccine, were; localized injection site pain, fatigue, headache, myalgia, and chills. In addition, the mRNA-1273 vaccine was also associated with; less than a 1-day change in the menstrual cycle, a 10-fold higher risk of myocarditis and pericarditis within young males aged 18-29 years and increased levels of anti-polyethylene glycol (PEG) antibodies. Expert Opinion The transient nature of commonly observed AEs and the rare occurrence of severe events within mRNA-1273 recipients show no significant safety concerns which should prevent vaccination. However, large-scale epidemiological studies with longer follow-up periods are required to surveillance rare safety outcomes.